Strand 1: Communication and collaboration on-line: New course models at the Open University - Alexander, Gary (Proceedings of the International Conference on Networked Learning, 1998)
This paper will describe the background and theoretical approach informing the design of a new course at the Open University, TI 71 Going Digital, now under development. It will pay particular attention to techniques for creating an effective online educational community. The course is the latest in a series of experimental courses, research prototypes and production courses which the author and his colleagues have developed over the past decade which have introduced collaborative and activity-based learning techniques to distance learning.